Iklan
Iklan

Penjelasan dengan langkah-langkah:

Metode Substitusi :

-- -- -- -- -- -- -- -- -- --

3x + y = 11 → y = -3x + 11 ... (i)

2x - 3y = -11 ... (ii)

Subs. y = -3x + 11 ke pers. (ii) :

  • 2x - 3y = -11
  • 2x - 3(-3x + 11) = -11
  • 2x + 9x - 33 = -11
  • 11x = -11 + 33
  • 11x = 22
  • x = 22/11
  • x = 2

Sub. nilai x = 2 ke pers. (i) :

  • y = -3x + 11
  • y = -3(2) + 11
  • y = -6 + 11
  • y = 5

Hp {(2, 5)}

Iklan
Iklan

Jawab:

   3x + y = 11  → x3 → 9x + 3y = 33

2x - 3y = - 11  → x1  → 2x - 3y = - 11

                                 ----------------- (+)

                                          11 x = 22

                                             x = 2

→  3x + y = 11

 3(2) + y = 11

           y = 11 - 6

           y = 5

HP = {2,5}

  • clarissa07azzahra
    terimakasih yaaaa
Iklan
Iklan